2019
DOI: 10.1002/ehf2.12401
|View full text |Cite
|
Sign up to set email alerts
|

Lung diffusion capacity in advanced heart failure: relation to central haemodynamics and outcome

Abstract: Aims Patients with heart failure (HF) are known to have a reduced pulmonary diffusion capacity for carbon monoxide (D LCO ), but little is known about how lung function relates to central haemodynamics. The aim of this study was to investigate the association between haemodynamic variables and pulmonary diffusion capacity adjusted for alveolar volume in congestive HF patients and to analyse how predicted D LCO /V A af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 25 publications
(51 reference statements)
0
16
0
Order By: Relevance
“…Heart failure can restrict lung volumes though pulmonary congestion, resulting in a reduced D LCO . Pulmonary congestion usually increases capillary blood volume, possibly contributing to the higher D LCO /V A values [40,45]. We showed that subjects with incident PRISm had a concomitant increase in BMI, independent of incident heart failure.…”
Section: Discussionmentioning
confidence: 60%
“…Heart failure can restrict lung volumes though pulmonary congestion, resulting in a reduced D LCO . Pulmonary congestion usually increases capillary blood volume, possibly contributing to the higher D LCO /V A values [40,45]. We showed that subjects with incident PRISm had a concomitant increase in BMI, independent of incident heart failure.…”
Section: Discussionmentioning
confidence: 60%
“…DLCO is reduced in patients with emphysema, pulmonary fibrosis, pulmonary hypertension, heart failure, mitral stenosis, and pulmonary oedema. [9][10][11][12] In this respect, patients with progressive heart failure have reduced DLCO, 9,10,13,14 and this decline in DLCO is associated with increased all-cause mortality. 13,15 In contrast, impairment of DLCO in patients with COPD is not associated with increased mortality.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12] In this respect, patients with progressive heart failure have reduced DLCO, 9,10,13,14 and this decline in DLCO is associated with increased all-cause mortality. 13,15 In contrast, impairment of DLCO in patients with COPD is not associated with increased mortality. [16][17][18] The association of reduced DLCO on outcome in cardiac surgery patients has only been explored in a few studies, including preselected groups of symptomatic patients with a history of smoking or use of bronchodilator/steroid treatment, and in this context, DLCO was associated with a worse outcome.…”
Section: Discussionmentioning
confidence: 99%
“…There is a higher mortality risk and poor prognosis in patients with heart failure that have low diffusing capacities (Deis et al, 2019;Hoeper et al, 2016;Nakamura et al, 2019). Thus, pulmonary function testing can sometimes occur frequently to help with patient management.…”
Section: Discussionmentioning
confidence: 99%
“…As pulmonary diffusing capacity is related to mortality risk and prognosis in patients with heart failure (Deis et al, 2019;Hoeper et al, 2016;Nakamura et al, 2019), it is measured frequently. As such, it would be essential to know the week-to-week variability (reproducibility) of pulmonary diffusing capacity for carbon monoxide (DLCO) and nitric oxide (DLNO).…”
Section: Introductionmentioning
confidence: 99%